2005
DOI: 10.1001/archpedi.159.6.572
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of Methylphenidate Treatment for Attention-Deficit/Hyperactivity Disorder

Abstract: Extended-release MPH formulations were associated with greater continuity of MPH treatment than IR formulations in the study population. Initial selection of an ER formulation may help to prolong continuity of MPH therapy among youth Medicaid beneficiaries with attention-deficit/hyperactivity disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
120
5
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(143 citation statements)
references
References 41 publications
16
120
5
2
Order By: Relevance
“…11,37,38 Qualitative methods, such as those employed in the current study, are essential to develop a richer understanding of this phenomenon. Parents in the current study and others 6,7,39,40 continue to experience fears and worries related to the potential for long-term adverse effects, even if their child shows marked improvement.…”
Section: Table 4 Domain 3: Continued Doubt and Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…11,37,38 Qualitative methods, such as those employed in the current study, are essential to develop a richer understanding of this phenomenon. Parents in the current study and others 6,7,39,40 continue to experience fears and worries related to the potential for long-term adverse effects, even if their child shows marked improvement.…”
Section: Table 4 Domain 3: Continued Doubt and Uncertaintymentioning
confidence: 99%
“…Despite the efficacy of medication to reduce ADHD symptoms, 10 medication initiation is variable, 1 and medication continuity is poor because many children stop taking medicine and/or have extended gaps in medication supply. 11,12 Although studies have identified child characteristics (eg, age, race) [11][12][13][14][15][16] and medication management factors (eg, dosing regimen) 11,16 related to medication continuity, factors that influence family decision-making have not been fully elucidated. The objective of this study was to better understand how parents make decisions about treatment for their child or adolescent with ADHD.…”
mentioning
confidence: 99%
“…40 In retrospective studies, stimulant persistence ranged from 59% at 4 months to 12%-43% at the end of 1 year. 10,13,[41][42][43] Antipsychotics might help to improve persistence to stimulant treatment through control of psychiatric comorbidities or behavioral symptoms of ADHD. On the other hand, the use of AAPs might lead to reduced efficacy of stimulants due to their opposite mechanism of action on the dopaminergic system.…”
Section: Predictors Of Concomitant Use Of Antipsychotics and Stimulanmentioning
confidence: 99%
“…The study cohort was identified using prescription claims for LAS (methylphenidate, dexmethylphenidate, mixed amphetamine salts, pemoline, and lisdexamfetamine dimesylate) and with at least 1 medical claim with a diagnosis of ADHD (ICD-9-CM code 314.xx) during the study period. 8,42,47,48 Index date was defined as the first prescription fill date of the first LAS from July 2004-December 2006. Cohort selection was limited to ADHD patients using LAS only because LAS are more frequently used in children and adolescents with ADHD than the other types of stimulants.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation